(untitled) (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study aimed to investigate the effect of antioxidants in the diet, vitamin E (V.E.), selenium (Se), and condensed tannins (COT), on growth performance, carcass characteristics, and certain physiological parameters of weaner rabbits. Materials and Methods: In a completely randomized design experiment, 105 weaning New Zealand White rabbits were reared from August to October (31.5°C ± 2°C) and fed a basal diet ad libitum for 8 weeks. They were then randomly assigned to seven nutritional treatments. As the control group, a basic diet devoid of antioxidants was used, while the other six groups were fed diets containing 100 or 200 mg V.E./kg, 0.1 or 0.2 mg Se/kg, and 1.5 or 3.0 gm COT/kg. Results: The findings showed that dietary interventions had no discernible impact on weight gain. The control group’s feed consumption (FC) was substantially higher than other treatments. In comparison to the control, the feed conversion ratio (FCR) increased (p < 0.05) with 0.1 mg Se/ kg diet (23.71%), V.E. 200 mg/kg diet (20.21%), 0.2 mg Se/kg diet (20.21%), and 1.5 gm COT/kg diet (15.27%). None of the dietary supplements under investigation had a discernible impact on the rabbits’ carcass characteristics or blood serum metabolites, except alanine aminotransferase (AST) and white blood cells (WBCs). While AST was enhanced after receiving COT 1.5 or 3.0 gm, Se 0.2 mg, and V.E. 200 mg/kg diet by 37.0%, 29.6%, 29.2%, and 29.0%, respectively, WBCs were reduced after receiving V.E. 200 mg/kg, Se 0.2 mg, and COT 3.0 gm/kg diet by 56.2%, 41.4%, and 29.13%, respectively. Conclusion: During the summer, feeding rabbits extra (V.E. 200 mg, Se 0.1 and 0.2 mg, or COT 1.5 and 3.0 gm/kg diet) appeared to help with FCR and FC. J. Adv. Vet. Anim. Res., 12(3): 740–750, September 2025 http://doi.org/10.5455/javar.2025.l937